European Code against Cancer, 4th Edition: Cancer screening. (December 2015) - Armaroli, Paola; Villain, Patricia; Suonio, Eero; Almonte, Maribel; Anttila, Ahti; Atkin, Wendy S.; Dean, Peter B.; de Koning, Harry J.; Dillner, Lena; Herrero, Rolando; Kuipers, Ernst J.; Lansdorp-Vogelaar, Iris; et al.
Abstract: In order to update the previous version of the European Code against Cancer and formulate evidence-based recommendations, a systematic search of the literature was performed according to the methodology agreed by the Code Working Groups. Based on the review, the 4th edition of the European Code against Cancer recommends: "Take part in organized cancer screening programmes for: Bowel cancer (men and women) Breast cancer (women) Cervical cancer (women)." Organized screening programs are preferable because they provide better conditions to ensure that the Guidelines for Quality Assurance in Screening are followed in order to achieve the greatest benefit with the least harm. Screening is recommended only for those cancers where a demonstrated life-saving effect substantially outweighs the potential harm of examining very large numbers of people who may otherwise never have, or suffer from, these cancers, and when an adequate quality of the screening is achieved. EU citizens are recommended to participate in cancer screening each time an invitation from the national or regional screening program is received and after having read the information materials provided and carefully considered the potential benefits and harms of screening. Screening programs in the European Union vary with respect to the age groups invited and to the interval between invitations, depending on each country's cancer burden, local resources, and the type of screening test used For colorectal cancer, most programs in the EU invite men and women starting at the age of 50–60 years, and from then on every 2 years if the screening test is the guaiac-based fecal occult blood test or fecal immunochemical test, or every 10 years or more if the screening test is flexible sigmoidoscopy or total colonoscopy. Most programs continue sending invitations to screening up to the age of 70–75 years. For breast cancer, most programs in the EU invite women starting at the age of 50 years, and not before the age of 40 years, and from then on every 2 years until the age of 70–75 years. For cervical cancer, if cytology (Pap) testing is used for screening, most programs in the EU invite women starting at the age of 25–30 years and from then on every 3 or 5 years. If human papillomavirus testing is used for screening, most women are invited starting at the age of 35 years (usually not before age 30 years) and from then on every 5 years or more. Irrespective of the test used, women continue participating in screening until the age of 60 or 65 years, and continue beyond this age unless the most recent test results are normal.